The determinants of capital structure of information technology firms in international market / Muhammad Firdaus Hariri Md Hamsani - Md Hamsani, Muhammad Firdaus Hariri (2017)
This research examines the determinants of capital structure of firms with a case study of manufacturing companies in information technology sector in international market from 2008 to 2015 with the purpose of providing a critical appraisal of the need and importance of capital structure. Descriptive and regression research technique was applied to test the impact of some key variables such as profitability, firm size, growth opportunity, tangibility and liquidity on firms value which is measured by total debt ratio (TDR) .In addition, secondary data was applied using data derived from nine (9) top information technology companies that have been sorted by forbes.com. To obtain the result, normality test and regression has been tested.